Deadline - Brown, Sandra, 1948- (New York : Grand Central Publishing, 2013)
Already coping with battle fatigue following his return from Afghanistan, journalist Dawson Scott receives a tip he cannot ignore about a potentially huge story involving the son of terrorists at-large for forty years.
Dawson Scott is a well-respected journalist recently returned from Afghanistan. Haunted by everything he experienced, hes privately suffering from battle fatigue which is a threat to every aspect of his life. But then he gets a call from a source within the FBI. A new development has come to light in a story that began 40 years ago. It could be the BIG story of Dawsons career one in which he has a vested interest. Soon, Dawson is covering the disappearance and presumed murder of former Marine Jeremy Wesson, the biological son of the pair of terrorists who remain on the FBIs Most Wanted list. As Dawson delves into the story, he finds himself developing feelings for Wessons ex-wife, Amelia, and her two young sons. But when Amelias nanny turns up dead, the case takes a stunning new turn, with Dawson himself becoming a suspect.
Keywords: Women novelists -- Fiction; Murder -- Investigation; Fiction; Family secrets -- Fiction; Secrets -- Fiction; Divorce -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Fiction; Mystery fiction